2017
DOI: 10.1140/epje/i2017-11555-y
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of polyetherimide thin films: Non-parametric dielectric response analysis with distribution of relaxation times

Abstract: High temperature polymeric materials for electrical insulation and energy storage are needed for transformational power applications such as pulsed-power and hybrid electrical vehicles. One of the candidate materials has been polyetherimide, an amorphous thermoplastic with a glass transition over 200 C. Here, the dielectric studies on the material are reported by taking into account the polarization and conduction processes in the polyetherimide. The dielectric data were analyzed with the distribution of relax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 69 publications
(131 reference statements)
0
7
0
Order By: Relevance
“…[ 108 ] More recently, Tuncer et al. [ 114 ] investigated the non‐parametric dielectric response of the PEI via a numerical inversion algorithm to solve the relaxation time distribution of the PEI films with a thickness of 5 µm. They revealed that the PEI is the potential for passive electrical component applications.…”
Section: Dielectric Polymers For Film Capacitorsmentioning
confidence: 99%
“…[ 108 ] More recently, Tuncer et al. [ 114 ] investigated the non‐parametric dielectric response of the PEI via a numerical inversion algorithm to solve the relaxation time distribution of the PEI films with a thickness of 5 µm. They revealed that the PEI is the potential for passive electrical component applications.…”
Section: Dielectric Polymers For Film Capacitorsmentioning
confidence: 99%
“…These polymers exhibit good chemical resistance, excellent electrical insulating properties, and high tensile strength over a wide temperature range. 7 show biocompatibility and low cytotoxicity which allow their use in bioapplication fields. 8,9 The characteristics of polyimides can be improved by using suitable monomers and the preparation of segmented copolymers containing flexible and rigid alternating segments.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the imide cycles impart good thermal stability, while the ether groups improve the solubility and reduce the glass transition and the softening temperatures of the polymers. These polymers exhibit good chemical resistance, excellent electrical insulating properties, and high tensile strength over a wide temperature range . They show biocompatibility and low cytotoxicity which allow their use in bioapplication fields. , …”
Section: Introductionmentioning
confidence: 99%
“…One alternative to these conventional methodologies is to use the distribution of relaxation times (DRT) [25][26][27][28][29][30][31][32], which interprets the impedance as resulting from a distribution of relaxation timescales, i.e., (1) where is the impedance, is the frequency, is the DRT, is a timescale variable, is a resistance, and is an inductance. The DRT model has proven to be very powerful, and recently this method has been employed to understand the fundamentals of solidstate ionic systems [33,34], batteries [35][36][37][38], supercapacitors [39,40], porous electrochemical reactors [41], dielectrics [42], solar cells [43], and fuel cells [44][45][46][47]. These applications have highlighted the promise of DRT models.…”
Section: Introductionmentioning
confidence: 99%